Efektifitas Penggunaan Media Konkret Terhadap Hasil Belajar Kognitif Matematika Siswa Sekolah Dasar Negeri Pandeanlamper 01 Semarang - Nor Muhammad Ali; Agnita Siska Pramasdyahsari; Ariestika Damayani; Paryati Paryati (Journal on Education, 2023)
This study analyses the effectiveness of concrete media in education in improving student learning. The research method used is a descriptive method by collecting data from various sources related to the use of concrete media in education. The results show that the use of concrete media in education can significantly improve students' learning outcomes, especially in the development of cognitive and critical thinking skills. Concrete media can also help to improve the efficiency and effectiveness of the learning process. However, the use of tangible media in education also poses challenges and risks that need to be well managed. Therefore, the use of concrete media in education should be carefully selected and integrated to achieve optimal results.